Under-Prescription of Medical Treatment for Peripheral Artery Disease in the Under 50s: A Retrospective Study - Soudet, Simon; Bultel, Lorène; Adnane, Lamrani; Reix, Thierry; Sevestre, Marie Antoinette (Angiology, 2022)
Peripheral artery disease (PAD) is a common cause of morbidity and mortality; however, data on its etiology and evolution in patients under 50 years old are scarce. Therefore, we performed a retrospective analysis of data from medical records, including cardiovascular risk factors, etiology, medical and surgical treatment, and follow-up. We included all patients with PAD aged between 18 and 50 years attending our university hospital between 2005 and 2015. Of the 87 patients included, 32 (36%) were women. Smoking was acknowledged by 81 patients (93%), and 37 had dyslipidemia (42.5%). Median follow-up was 24 months (10-59). Recurrence occurred in 41 patients (47.1%), all active smokers, with a median delay of 14 months (7-47). Acute limb ischemia at diagnosis was significantly associated with major amputation, odds ratio (OR) 5.95 (95%CI 1.41-40.90, = .029), which was needed by 11 patients (12.6%). Treatments included antiplatelet therapy (76; 87.4%), statins (67; 77%), and anti-hypertensives (60; 69%), and 29 (32.1%) patients benefited from vascular rehabilitation. This cohort of relatively young patients with PAD showed a high level of symptom recurrence. Atherosclerosis was the most common etiology. Our study revealed that medical treatment is often under-prescribed in this age group and needs to be improved.